The Role of the Cyber Crime Unit of the North Sumatra Regional Police in Overcoming Online Fraud Crime in North Sumatra - Hafizsyah, Muhammad; Marpaung, Zaid Alfauza (Jurnal Daulat Hukum, 2024)
The rise of online fraud crimes in North Sumatra has caused financial losses to victims. This study aims to determine the role of law enforcement of the cybercrime unit of the North Sumatra regional police and its obstacles to the perpetrators of online fraud. The method used is empirical legal research whose sources are obtained from primary, secondary and tertiary data which are then analyzed qualitatively. The results of the study found that significant challenges faced by investigators in handling online fraud cases. Difficulties in identifying perpetrators who use fake identities and often change places are the main obstacles that slow down case resolution. These obstacles show the complexity of the mode of operation used by the perpetrators, which requires sophisticated and adaptive handling strategies from the police. Preventive and repressive efforts carried out by the Cyber Unit of the North Sumatra Police Ditreskrimsus are the right steps in tackling online fraud. Strict supervision of social media, counseling to the public, and takedowns of content containing elements of fraud are proactive steps that can prevent further fraud. In addition, the resolution of outstanding reports demonstrates the police's commitment to providing a sense of security to the community. However, the success of this effort also depends on good cooperation between the community and the police. Continuous education to the public on the dangers of online fraud and how to prevent it is essential to reduce the number of victims. In this digital era, increasing the capacity and skills of investigators in information technology is also a crucial factor in dealing with increasingly sophisticated criminals. Overall, this study emphasizes the importance of a holistic and integrated approach in tackling online fraud crimes.